News media coverage of smoking and health is associated with changes in population rates of smoking cessation but not initiation. Issue 2 (1st June 2001) - Pierce, John P; Gilpin, Elizabeth A
Abstract : OBJECTIVE: To determine whether changes in news media coverage of smoking and health issues are associated with changes in smoking behaviour in the USA. DESIGN AND MAIN OUTCOME MEASURES: Issue importance in the US news media is assessed by the number of articles published annually in major magazines indexed in The Reader's Guide to Periodical Literature . Annual incidence rates for cessation and initiation in the USA were computed from the large, representative National Health Interview Surveys (1965–1992). Patterns in cessation incidence were considered for ages 20–34 years and 35–50 years. Initiation incidence was examined for adolescents (14–17 years) and young adults (18–21 years) of both sexes. RESULTS: From 1950 to the early 1980s, the annual incidence of cessation in the USA mirrored the pattern of news media coverage of smoking and health, particularly for middle aged smokers. Cessation rates in younger adults increased considerably when secondhand smoke concerns started to increase in the US population. Incidence of initiation in young adults did not start to decline until the beginning of the public health campaign against smoking in the 1960s. Among adolescents, incidence rates did not start to decline until the 1970s, after the broadcast ban on cigarette advertising. CONCLUSIONS: The level of coverage of smoking and health in the news media may play an important role in determining the rate of population smoking cessation, but not initiation. In countries where cessation has lagged, advocates should work to increase the newsworthiness of smoking and health issues.